(untitled) (Bangladesh Journal of Child Health, 2023)
Background: Malnutrition and cancer both influences tolerance and response to treatment especially ALL. Malnutrition increases morbidity, mortality, reduces the effectiveness of treatment and impairs the quality of life significantly. Objective: Assessment of the nutritional status and its influence on treatment outcome children with Acute Lymphoblastic Leukemia (ALL) before and after induction chemotherapy. Materials & Methods: This prospective observational study included 72 children with ALL, aged 1-15 years, was conducted from January to December 2014 in the Department of Pediatric Hematology and Oncology, BSMMU. The anthropometric measurements (weight-for-age, height-for-age, weight-for-height, MUAC, BMI) hematological and biochemical parameter (serum albumin, total protein) were measured. The children got induction chemotherapy according to the UK ALL 2003 (modified) protocol. Results: Among the study population, 18(39.1%) were underweight, 8(17.4%) were stunted, 16(34.8%) were wasted, MUAC for age 14(56.0%) and BMI for age 12(57.1%) were malnourished, 10.9% had low total proteins (<5.7g/dl), 37.0% low serum albumin (<3.2g/dL). Mean anthropometric measurements and biochemical parameters were higher among the survivors compared to non-survivors. Significant difference was found between the well-nourished and the malnourished group according to WAZ. Complications like febrile neutropenia, treatment delay, number of transfusion (PRBC) requirement were more in malnourished group. Conclusion: Malnutrition is widely prevalent in children with ALL and a major determining factor in treatment planning, complications and final outcome. BANGLADESH J CHILD HEALTH 2022; VOL 46 (1) : 3-8